Subliminal advertising - the measurement of the effectiveness of three mainstream subliminal ad contents from a cultural perspective - Li, Qiutong (2019)
This empirical study examines three types of advertising that are most commonly considered to be subliminal advertising, which are: sexual ad, metaphor ad, and celebrity endorsement ad. These three types of advertising have been widely studied separately in their own realm, but the purpose of this study is to compare them to each other to find out which one works best. This study selects existing advertisings from the real market and tries to make them satisfy the needs of this experiment as much as possible to complete a more empirical study that testing the real effects of existing advertisings in certain consumer groups. In the experiment, 55 Chinese international students from the University of Nottingham Business School were sampled. They were exposed to four selected advertisings (one of which was a blank control group) and followed by a descriptive self-report questionnaire using 7-point Likert scale to measure their attitudes and purchase intentions toward each type of advertising. The answers of the questionnaire were analyzed in SPSS by MANOVA, independent sample T-test and multiple regression. The results reveal that celebrity endorsement ad is the only statistically significant superior among the three tested advertisings in both improving attitudes and promoting purchase intentions, while the other two types of advertising are effectless. This outstanding performance of celebrity endorsement advertising is mainly reflected in the female group, while males show no obvious additionally positive response. This result could also be attributed to the difference of advertising stimuli selected for the different genders. Finally, regression analysis indicates that attitude variables might work in different ways that vary from different types of advertising. Only favor is the universal significant positive predictor.